Classroom Action Research on Thematic-Designed Online Learning for Contemporary Japanese Literature - Hayun Nurdiniyah; Wafa' Hanim Askho; Ari Artadi (Universitas Diponegoro, 2021)
This study aims to implement contemporary Japanese literature learning with thematic designs as a learning strategy for 60 students in literary study classes (Poetry, Prose, and Drama) at Darma Persada University that were conducted online during the pandemic. This study was conducted using Kurt Lewin's Classroom Action Research model consisting of planning, acting, observing, and reflecting; particularly for the observing section, the assessment was measured using two indicators based on students’ understanding of the material and satisfaction with online learning. Data was collected using questionnaires and filled out via google form. The findings of this study indicate the level of student understanding of the material, the constraints of online learning, and feedback from experts. The findings are useful for improving Japanese literature learning, to be more precisely during the online course